Detection of elephant endotheliotropic herpesvirus (EEHV) in Asian (Elephas maximus) and African elephants (Loxodonta africana) - Kotila-Row, Anna (2015)
Elephant endotheliotropic herpesvirus (EEHV) has been identified as the cause of rapid onset acute hemorrhagic disease. EEHV infects both Asian (Elephas maximus) and African elephants (Loxodonta africana). The virus has been detected in wild and captive populations. Seven different genotypes of EEHV have been identified so far. EEHV1 is recognized as the most common cause of acute disease, and more rarely EEHV3 and EEHV4. EEHV-associated disease is most common in juvenile Asian elephants. Primary infection can be either subclinical or cause the disease. EEHV can persist in the host in latent phase and reactivate from time to time. Data collection from ex situ elephants worldwide, suggest that subclinical EEHV1 infections are common in captivity. Subclinical infections may occur in situ also. An elephant with subclinical infection can shed the virus particles into a range of the host fluids. The infected fluids may have the potential to transmit a virus to other elephants in contact with the host. To be able to manage this devastating disease it is essential to identify animals with subclinical or latent infections. It is also critical to diagnose animals with acute disease immediately after the first symptoms appear. Reliable, specific, fast and easy to use diagnostic tools are much needed. Currently available diagnostic tools and new possible methods such as quantitative real-time PCR, antibody based detection, acute phase protein expression, viral microRNA detection and ultrasound-guided biopsy sampling are described in this review.